A methodological approach to compare continuous and instantaneous sampling and two methods to deal with animals out of sight on dairy cattle behavior and interaction with their calf in the first hours post-partum - Manfrè, Claudia; Battini, Monica; Simonetto, Alberto; Contiero, Barbara; Serva, Lorenzo; Mattiello, Silvana; Ntalampiras, Stavros; Normando, Simona; Brscic, Marta (Frontiers in Veterinary Science, 2024)
Animal behavior can provide useful information about animal welfare, but methods and tools used to gather behavioral data and data treatment can influence the results. Therefore, this study was carried out on dairy cow (Bos taurus) behavior and interaction with calves early post-partum aiming at comparing two sampling rules, namely continuous and instantaneous sampling at scan intervals of 30 seconds, 1, 2, 3, 4, 5, and 10 minutes, and two methods to deal with out of sight animals. The study was based on three assumptions: 1) continuous sampling provides the most complete and accurate data, allowing the observation of seldom behaviors and short events; 2) instantaneous sampling can provide accurate measurements of frequency and duration, especially at short scan intervals; 3) differences in behavioral results may occur depending on whether a correction for time out of sight is applied or not. Thus, ten dams were observed from videos in the two hours post-parturition. Ruminating, stereotypies, calf-biting and calf-butting were not recorded during the observation period. Other behaviors were observed only with continuous sampling or with continuous and instantaneous at 30-second scan intervals. The recoding of several behaviors was less accurate when applying longer scan intervals. Data from continuous and instantaneous sampling at 30-second scan intervals were compared with Wilcoxon test. Results showed no significant differences for posture, position in the pen and all behaviors (P>0.05) except vocalizing (P=0.003). The same test did not highlight significant differences due to method of dealing with out of sight for both sampling rules (P>0.05). Correlation between continuous and instantaneous sampling were prevalently high at 30-second intervals and they decreased as the length of scan intervals increased for most behaviors. Results confirmed the first two assumptions suggesting that continuous sampling is more accurate, in particular for short and rare behaviors, and caution against the suitability of dam behavioral data collected using instantaneous sampling at scan intervals of minutes. The third assumption was not proven by this study. Results should be considered in light of the development of new technologies that relies on data acquired by sensors and imaging to monitor cow-calf welfare and behavior post-parturition.